Specificity of reversible ADP-ribosylation and regulation of cellular processes. (2nd January 2018) - Crawford, Kerryanne; Bonfiglio, Juan José; Mikoč, Andreja; Matic, Ivan; Ahel, Ivan
Abstract: Proper and timely regulation of cellular processes is fundamental to the overall health and viability of organisms across all kingdoms of life. Thus, organisms have evolved multiple highly dynamic and complex biochemical signaling cascades in order to adapt and survive diverse challenges. One such method of conferring rapid adaptation is the addition or removal of reversible modifications of different chemical groups onto macromolecules which in turn induce the appropriate downstream outcome. ADP-ribosylation, the addition of ADP-ribose (ADPr) groups, represents one of these highly conserved signaling chemicals. Herein we outline the writers, erasers and readers of ADP-ribosylation and dip into the multitude of cellular processes they have been implicated in. We also review what we currently know on how specificity of activity is ensured for this important modification.